Analiza procesu planowania strategicznego w korporacjach z uwzględnieniem logistyki - Lisiński, Marek; Pająk, Wojciech (Analysis of the Strategic Planning Process in Corporations with Taking into Account Logistics, 2005)
The aim of the article is to present the procedure of the strategic planning process and to define the place and the role of logistics within it.The suggested model assumes, that the strategic planning process takes place at three levels, which are: the corporation, the individual strategic business units and the basic functional units (including logistics). It also presents how the tasks of a strategic planning are distributed on the different hierarchical levels and the relations between the subjects that seek to complete those tasks.The nature of the presented model is not universal, therefore, depending on the characteristics of the company (size, product and technology complexity, structural solutions, personnel) it can be modified.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 90-98